THE STUDENTS’ ATTITUDE TOWARDS GOOGLE TRANSLATE - Martina Mulyani; Fakhrunisa Afina (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
Google Translate (GT) is a tool commonly used by those who learn translation in higher education. While the research on GT mostly evaluated GT through experimental design, very few studies have focused on student perceptions of GT. Hence, this research intends to investigate their students’ attitudes of GT performance. 24 students of higher education in Cimahi participated in the study. The data about students’ attitude include behavior, cognitive, and affective attitude. They were gathered through questionnaire and interview. The result revealed that in behavioral attitude, the students’ often use GT to check the meaning of unknown word and translating a sentence. Meanwhile, the cognitive attitude indicated that few students assume that GT is ethically acceptable regardless of how it is used because it is helpful in the language learning process. In the affective attitude, GT is positive because they felt like using GT in translation. Even, some of them felt helped by GT’s assistance and the other reason was GT was easy to use. In short, student’s regard GT as a useful tool in translation depending on the way how one uses the tool.